ENHANCING ECONOMIC RESILIENCE: AN EVIDENCE-BASED POLICY FRAMEWORK FOR ACEH UTARA'S EMBROIDERY ARTISANS - Adawiyah, Rabiatul; Farida, Ratna; Syukri, Syukri; Marzuki, Marzuki (Natapraja, 2025)
This study aims to analyze the economic resilience of embroidery artisans in North Aceh Regency and to develop an evidence-based policy framework tailored to local needs. The research employed a concurrent mixed-methods approach by integrating quantitative and qualitative data collected through semi-structured questionnaires administered to 110 embroidery artisans in Muara Batu District. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic coding. The findings reveal that, overall, the artisans’ economic resilience falls within the moderate category, with an average score of 2.69 on a four-point scale. Two dimensions, namely business capacity and household economic resilience, remain at a moderate level, whereas access to capital and technology, as well as institutional networks, appear relatively stronger. The results also highlight vulnerabilities in income stability, emergency savings, and limited access to financing and business training. On the other hand, artisans demonstrate notable strengths in product innovation, digital marketing adoption, and openness to customer feedback. Based on these results, the study emphasizes the importance of strengthening community institutions, expanding access to financial resources, promoting digital-based marketing, and fostering multi-stakeholder collaboration as key strategies to enhance economic resilience. This research contributes by providing empirical evidence that can serve as a foundation for formulating evidence-based policies in the craft sector, thereby ensuring that interventions are more contextual, adaptive, and sustainable.